Your emotions, yourself : a guide to your changing emotions - Virtue, Doreen, 1958-; Brokaw, Tanya (Los Angeles : Lowell House Juvenile ; Chicago : Contemporary Books, 1996)
Examines some of the feelings experienced by young people and discusses how to deal with painful emotions and get help when needed.
Includes index.
Keywords: Emotions in children -- Juvenile literature; Emotions in adolescence -- Juvenile literature; Emotions